Pengaruh Harga, Pelayanan Dan Promosi Terhadap Keputusan Pengguna Pada Aplikasi Grab (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2020) - Abdillah, Muhammad Yusuf Ulwan; Wahono, Budi; Basalamah, Muhammad Ridwan (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
AbstractÂ This study aims to test and explain the effect of price, service and promotion on user decisions on the Grab application (Case Study of Students of the Faculty of Economics and Business, Islamic University of Malang Class of 2020). This research is a type of quantitative research. The method used is multiple linear regression. The sampling technique using the formula from Solvin with the results of the calculation of 88 samples. To solve the problems in this study using SPSS assistance with validity tests, reliability tests, normality tests, multiple linear regression analysis, multicollinearity tests, heteroscedasticity tests, F tests, and t tests. The results showed that simultaneously. Price (X1), Service (X2), Promotion (X3) variables simultaneously have a significant effect on User Decisions on the Grab Application (Y). And there is a partial influence between Price (X1), Service (X2), Promotion (X3) on User Decisions on the Grab Application (Y).Â Keywords: Price, Service, Promotion, User Decision